2014
DOI: 10.1038/eye.2014.48
|View full text |Cite
|
Sign up to set email alerts
|

Is it safe to discharge treated proliferative diabetic retinopathy patients from the hospital eye service to a community screening programme?

Abstract: Purpose To investigate the distribution of new vessels (NV) in patients treated with pan-retinal photocoagulation for proliferative diabetic retinopathy (PDR). To assess whether it is safe to discharge treated PDR patients to the NHS Diabetic Eye Screening Programme (DESP) which uses two mydriatic 451 fields of each eye. Methods Consecutive treated PDR patients undergoing fundus fluorescein angiography between July 2010 and October 2011 for the purpose of looking for NV were included. The distribution of NV wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…HES have access to wide field fundus imaging, whereas, DRS use two 45-degree field images. Negretti et al observed 108 eyes and found that 17% of NVE were outside of the DRS imaging fields and 11% of patients with active PDR would have been missed [ 23 ]. However, despite DRS not having 100% sensitivity it is considered a safe and effective screening tool to detect PDR.…”
Section: Discussionmentioning
confidence: 99%
“…HES have access to wide field fundus imaging, whereas, DRS use two 45-degree field images. Negretti et al observed 108 eyes and found that 17% of NVE were outside of the DRS imaging fields and 11% of patients with active PDR would have been missed [ 23 ]. However, despite DRS not having 100% sensitivity it is considered a safe and effective screening tool to detect PDR.…”
Section: Discussionmentioning
confidence: 99%
“…HES have access to wide eld fundus imaging, whereas, DRS use two 45-degree eld images. Negretti et al observed 108 eyes and found that 17% of NVE were outside of the DRS imaging elds and 11% of patients with active PDR would have been missed 7 . However, despite DRS not having 100% sensitivity it is considered a safe and effective screening tool to detect PDR.…”
Section: Discussionmentioning
confidence: 99%